Revue des Deux Mondes. (Paris, 1927)
Bibliotheek E. Anseele
Periodiciteit: tweewekelijks
Hoofdredactie: René Doumio (directeur-gérant)
Redactie: L. Bertrand (de l'Académie française), C.J. Diamandy, André Maurois, Edith Wharton, Paul Hazard, Maurice Levaillant, Victor Forlin, André Gavoty, René Doumic, René Pinon
Beheer/Administratie: rue de l'Université 15, Paris-7e
Drukker/Drukkerij: Typ. Philippe Renouard, rue des Saints-Pères 19, Paris
Frans